An Experimental Study on the Compressive Dynamic Performance of Polypropylene Fiber Reinforced Concrete for Retaining Structure under Automobile Collision Magnitude - Furong Li; Guoxing Chen; Guizhong Xu; Yongyi Wu (Advances in Civil Engineering)
In order to examine the compressive dynamic performance of polypropylene fiber reinforced concrete to be used for the retaining structure under the automobile collision magnitude, an experimental study was carried out by using hydraulic servo on concrete specimens with 4 different polypropylene fiber contents under 6 loading strain rates. The failure modes and stress-strain curves of concrete under different loading conditions were obtained. Then, by comparatively analyzing the mechanical characteristic parameters of polypropylene fiber reinforced concrete under different loading conditions, the following conclusions are drawn: with the increase of the polypropylene fiber content, the integrity of concrete upon compressive failure is gradually improved. When the polypropylene fiber content is relatively high, the static and dynamic failure modes are basically similar. With the increase of the loading strain rate, the peak compressive stress and elastic modulus of the polypropylene fiber reinforced concrete gradually increase. The increase in the polypropylene fiber content gradually intensifies the effect of loading strain rate on the peak compressive stress dynamic improvement coefficient. The peak strain of polypropylene fiber reinforced concrete is gradually increased with the increase of polypropylene fiber content, while the effect of the loading strain rate on the peak strain shows an obvious discreteness characteristic. Meanwhile, we proposed a relationship equation for describing the peak compressive stress dynamic improvement coefficient based on the coupling effect of the polypropylene fiber content and loading strain rate and further discussed the underlying stress mechanism in detail. Our research findings are of important research significance for the application and promotion of polypropylene fiber reinforced concrete in the engineering practice of retaining structures.